The prevalence and associated factors responsible for delayed return to work after the mandatory isolation period post-Covid-19 at Tygerberg Hospital, 2020 a cross-sectional study - Weinand, Fredrick John (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMed)--Stellenbosch University, 2022.